Evaluation of Oral Health Status and behavior of Children with Autism Spectrum Disorder in Derna, Libya - Abdalhalem F. Rages; Mohamed F. Rafa; Marwa G. Faleh; Mira A. Almaryme (African Journal of Advanced Pure and Applied Sciences, 2023)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder that constitutes a multifactorial problem that affect all aspects of affected children. One of these problems is the oral health including the daily oral health activities, the access to dental care, as well as the associated habits that influence oral health. The aim of this study was to evaluate oral health status and behavior of children with autism spectrum disorder in Derna city, Libya. The study included 51 children from two specialized centers in the city. Data collected from their parents using a questionnaire. The questionnaire assessed oral care at home, access to dental care and dental symptoms and behaviors. The study found that the majority of children 76.6% need help during tooth brushing. They are not regularly got access to dental care as around 49% of them are visiting the dentist only when needed. The most frequent reasons to seek dentists were tooth pain and carries 44.4% and 25% respectively. 47.2% of parents reported that the dental visits were hard and unpleasant time. In conclusion autistic children have several multifactorial barriers to appropriate oral hygiene as well as access to dental care. More attention is needed from the health care services for autistic children and their families to overcome these barriers.